Apolipoprotein E imbalance in the cerebrospinal fluid of Alzheimer’s disease patients - Matthew Paul Lennol; Irene Sánchez-Domínguez; Inmaculada Cuchillo-Ibañez; Elena Camporesi; Gunnar Brinkmalm; Daniel Alcolea; Juan Fortea; Alberto Lleó; Guadalupe Soria; Fernando Aguado; Henrik Zetterberg; Kaj Blennow; et al. (Alzheimer’s Research & Therapy)
Abstract Objective The purpose of this study was to examine the levels of cerebrospinal fluid (CSF) apolipoprotein E (apoE) species in Alzheimer’s disease (AD) patients. Methods We analyzed two CSF cohorts of AD and control individuals expressing different APOE genotypes. Moreover, CSF samples from the TgF344-AD rat model were included. Samples were run in native- and SDS-PAGE under reducing or non-reducing conditions (with or without β-mercaptoethanol). Immunoprecipitation combined with mass spectrometry or western blotting analyses served to assess the identity of apoE complexes. Results In TgF344-AD rats expressing a unique apoE variant resembling human apoE4, a ~35-kDa apoE monomer was identified, increasing at 16.5 months compared with wild-types. In humans, apoE isoforms form disulfide-linked dimers in CSF, except apoE4, which lacks a cysteine residue. Thus, controls showed a decrease in the apoE dimer/monomer quotient in the APOE ε3/ε4 group compared with ε3/ε3 by native electrophoresis. A major contribution of dimers was found in APOE ε3/ε4 AD cases, and, unexpectedly, dimers were also found in ε4/ε4 AD cases. Under reducing conditions, two apoE monomeric glycoforms at 36 kDa and at 34 kDa were found in all human samples. In AD patients, the amount of the 34-kDa species increased, while the 36-kDa/34-kDa quotient was lower compared with controls. Interestingly, under reducing conditions, a ~100-kDa apoE complex, the identity of which was confirmed by mass spectrometry, also appeared in human AD individuals across all APOE genotypes, suggesting the occurrence of aberrantly resistant apoE aggregates. A second independent cohort of CSF samples validated these results. Conclusion These results indicate that despite the increase in total apoE content the apoE protein is altered in AD CSF, suggesting that function may be compromised.